APPRAISAL ANALYSIS IN FREEDOM WRITERS MOVIE - Nani Hidayati (EduLite: Journal of English Education, Literature and Culture, 2017)
This study attempts to find out conveyed messages in the movie from the realization of the appraisal and narrative structure as well as to describe the use of the Appraisal System to express LaGravenese's (a) Attitudes, (b)Engagement & (c) Graduation towards the main characters in Freedom Writers movie screenplay. Using both quantitative and qualitative descriptive approach for discourse appraisal system analysis, the result of this study reveals several messages of tolerance, earning respect and trust, honor diversity, and striving for success and trust from the realization of Appraisal and Narrative Structure either in the dialogues or monologues of Freedom Writers’ characters. The result from the Appraisal Devices realizing (a) Attitudes reveals that LaGravenese likes to express characters’ negative emotion explicitly than implicitly. He likes to express characters’ negative capability than other kinds of Judgments. He appreciates the characters using more Negative Value which denotes that in his opinion, they see each other negatively. (b)Engagement used in the screenplay describes that he emphasizes more on characters’ denial towards each other’s opinion and existence with the use of more Disclaim Heterogloss in the screenplay. (c)Graduation used in the screenplay describes that the use of more Sharpening Focus indicates he emphasizes on characters’ category boundary more than scaling of intensity.Keywords: Appraisal Devices, Attitude, Engagement, and Graduation.